PERFORMANCE OPTIMIZATION OF A COMBINED SOLAR COLLECTOR, GEOTHERMAL HEAT PUMP AND THERMAL SEASONAL STORAGE SYSTEM FOR HEATING AND COOLING GREENHOUSES - Ataei, Abtin (Journal of Applied Engineering Science, 2016)
In this research, optimum design of a combined solar collector, geothermal heat pump and thermal seasonal storage system for heating and cooling a sample greenhouse is studied. In order to optimize the system from technical point of view some new control strategies and functions resulting from important TRNSYS output diagrams are presented. Temperatures of ground, rock bed storage, outlet ground heat exchanger fluid and entering fluid to the evaporator specify our strategies. Optimal heat storage is done with maximum efficiency and minimum loss. Mean seasonal heating and cooling COPs of 4.92 and 7.14 are achieved in series mode as there is no need to start the heat pump sometimes. Furthermore, optimal parallel operation of the storage and the heat pump is studied by applying the same control strategies. Although the aforementioned system has higher mean seasonal heating and cooling COPs (4.96 and 7.18 respectively) and lower initial cost, it requires higher amounts of auxiliary energy either. Soil temperature around ground heat exchanger will also increase up to 1.5 ̊C after 2 years of operation as a result of seasonal storage. At the end the optimum combined system is chosen by trade-off between technical and economical issues.